The Abilities of Salidroside on Ameliorating Inflammation, Skewing the Imbalanced Nucleotide Oligomerization Domain-Like Receptor Family Pyrin Domain Containing 3/Autophagy, and Maintaining Intestinal Barrier Are Profitable in Colitis - Liu, Jiuxi; Cai, Jiapei; Fan, Peng; Zhang, Naisheng; Cao, Yongguo (Frontiers in Pharmacology, 2019)
Salidroside (Sal), as a major glycoside extracted from Rhodiola rosea L, has exhibited its mighty anti-aging, anti-oxidant, anti-cancer, anti-inflammation and neuroprotective effects in many diseases. Recently, it has showed its protective effect in colitis mice by activating the SIRT1/FoxOs pathway. Whereas, it is not known whether salidroside has other protective mechanisms on dextran sulfate sodium (DSS)-induced colitis in mice. In this study, we investigated the protective effects and mechanisms of Sal on DSS-induced colitis in mice. The results demonstrated Sal was a competent candidate in the treatment of ulcerative colitis (UC). Sal remitted DSS-induced disease activity index (DAI), colon length shortening and colonic pathological damage. Simultaneously, Sal alleviated excessive inflammation by reversing the IL-1β, TNF-α and IL-10 protein levels in DSS-treated mice. Western blot analysis revealed that Sal inhibited p65 and p38 activation together with PPARγ up-regulation. In addition, Sal skewed the imbalanced activation of NLRP3 inflammasome and autophagy contributing to colitis recovery. The damaged intestinal barrier induced by DSS was also alleviated along with plasma LPS reduction after Sal treatment. In vitro, Sal showed PPARγ-dependent anti-inflammatory effect in LPS-stimulated RAW264.7 cells. In summary, our results demonstrated that Sal might be an effective factor for UC treatment and its pharmacological value deserved further development.